Digital Learning Implementation Using Kahoot Application on Biotechnology of Plant in Mattayom 1 - Rif’atul Fitri Supa’at; Erlia Narulita; Kanoklada . (BIOEDUKASI, 2018)
Kahoot is a relatively new e-learning education tool.The data on its effectiveness in classroom teaching for plant biotechnology is scarce and limited. Hence the current research was aimed at incorporating Kahoot in classroom activity in plant biotechnology learning and to assess the effectiveness of Kahoot in the learning process. Qualitative research method was adopted in this study to investigate the applicability of the Kahoot!, the digital assessment tool, in Mattayom 1 (1st Grade Junior High School). Using data collection methods such as qualitative research , observation, document analysis. There are 45 Participants from Mattayom 1/12 in Hatyaiwittayalaisomboonkulkannya School. Based on pre test and post test average value we can assessed effectiveness of Kahoot as an e-learning tool in Biotechnology learning. Pre test is assessment before using Kahoot. We can see that before we used Kahoot average value of test is 55,95 and after we used Kahoot average value of test is 81,92. Kahoot has made students’ learning easy, enjoyable, and interactive and helped them to understand the subject better. Kahoot is an excellent e-learning tool that provides a positive environment in the classroom, increases energy, concentration, and knowledge. It can motivate the students to learn in a fun filled, enjoyable, and friendly competitive environment. Key words: Kahoot, Digital learning, Assessment.